THE DYNAMICS OF THE POPULATION OF MONOCITIES IN UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
The article analyzes the periodic changes in the population dynamics of Uzbekistan’s monocities during the years of independence, their relationship with general development trends and socio-economic factors, reveals the specific features of demographic processes across different functional types of cities, and examines the influence of industrial sectors, changes in the administrative status of certain cities, natural population growth, and migration movements on population size.